Experimental evaluation of strength degradation of orthodontic chain elastics exposed to cigarette combustion smoke - Ferraz, Caio; Mathias, Paula; Costa, Matheus; Pithon, Matheus; Braga, Emanuel (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2020)
Introduction: Effects of cigars in the performance of dental restorative materials have been largely investigated; however, no information about the role of smoking cigars in strength degradation of orthodontic elastics has been revealed. Aim of the study: evaluate the effect of smoke derived from cigarette combustion on the strength degradation of orthodontic chain elastics. Materials and methods: Four distinct elastics from two different manufacturers were evaluated: Maximum Power Chain Pearl (OTP) (OrthoTechnology); Maximum Power Chain Pearl Tone Blue (OTPB) (OrthoTechnology); Orthodontic Elastic Chain Gray (MG) (Morelli); Orthodontic Elastic Chain Crystal (MC) (Morelli). Elastic segments were distended and exposed for eight minutes, twice a day with interval of 12 hours to cigarette combustion smoke. Elastic tension was evaluated at baseline, 7, 14 and 21 days. Results: the findings have shown that all elastics presented progressive tension reduction over the period evaluated. Statistically significant differences were evidenced from the baseline to 7 days and from 14 to 21 days period. The OTP and OTPB elastics presented greater initial tension when compared to the MG and MC elastics. This pattern was reproduced throughout the study periods. When test groups were compared to the control in the period of 21 days, it was observed that cigars combustion smoke reduced in a statistically significant manner the elastic strength in all groups tested. Relative comparisons between the tested samples and control in the period of 21 days indicated that smoke exposure promoted strength loss that varied from 7% (OTP) to 12% (OTPB). Conclusion: experimental exposure to cigarettes combustion smoke contributed for the strength degradation of orthodontic chain elastics in the period of 21 days.
Keywords: Force Degradation; Elastomers; Tobacco Products; Orthodontics